Na roça, na mesa, na vida: uma viagem pelas rotas e desvios da mandioca ao fazer-se coisas de comer, no e além do nordeste paraense - Picanço, Miguel de Nazaré Brito (Universidade do Vale do Rio dos Sinos, 2018)
This ethnography is inscribed in contemporary studies dealing with material culture and collective life, considering the trajectories and movements of some species of the natural world cultivated by individuals. Thus, I seek to study the re-significances that are taking place in contemporary material culture, in an order of interaction between the elements, things and species of nature that make up this material culture, and their experiences with humans and non-humans (Ingold, 2015, 2012; Gell, 2005). Through ethnographic incursions, based on participant observations, formal and informal conversations, I studied the trajectories and movements of cassava and its routes and deviations (Appadurai, 2008) in and beyond the Brazilian territory, with centrality in the State of Pará, where it populate a tangle of commercial, commensal, and religious practices with and among the subjects who cultivate it, establishing itself as a primordial food and as an object in the constitution of experiences that populate the daily life of the Paraense. Therefore, this research aimed to analyze and describe the experiences of cassava with the humans that inhabit the text of the research, and of these with it. To this end, I set out to follow the materials and people that give concrete expression to the above mentioned experiences in order to: ethnograph the processes that culminate with the production, consumption and singularization (Kopytoff, 2008) of the descendants of cassava, as well as recognize as these experiences are negotiated and established.
Keywords: Mandioca; Cultura material; Singularização; Comensalidades; Sociabilidades; Cassava; Material culture; Singulization; Commensalities; Sociabilities; ACCNPQ::Ciências Humanas::Sociologia